Pembelajaran Prakarya sebagai Sarana Pengembangan Keterampilan dan Kreativitas Siswa di MTsN 8 Jakarta - Jihan Zalika Rachman; Siska Maulidya (Pusat Riset dan Inovasi Nasional, 2025)
Workshop learning has great potential in developing students' skills and creativity, especially at the secondary education level. This study aims to analyze the implementation of workshop learning at MTs Negeri 8 Jakarta as a means of developing students' skills and creativity. Using a qualitative-descriptive approach, data were collected through observations, interviews, and document studies related to the learning process. The results show that workshop learning is able to improve students' ability to create innovative products that are aesthetically and economically useful. In addition, this learning also encourages students to think original, flexible and elaborative. However, the implementation of this learning still faces various obstacles, such as limited facilities, teaching materials, and less varied learning methods. Therefore, contextual innovative learning strategies are needed to optimize students' potential. In addition, workshop learning is also an effective platform for instilling local cultural values and entrepreneurship. This article provides recommendations on developing a more effective approach to workshop learning, including improved facilities, development of teaching materials, and implementation of project-based learning methods. Thus, workshop learning can be a medium that not only improves students' skills and creativity but also prepares them to contribute actively in society.